Anxiety of students with visual impairment in school for visually impaired students in Thailand - Leksaranyaphong, Penphitcha; Suppapitiporn, Siriluck (Chulalongkorn Medical Journal, 2021)
Background: Anxiety is a prominent cause of mental health issues in students. Studies on this in the visual impairment are limited and none has been conducted in Thailand. The researcher finds that mental health in visually impaired students is significant and the study should be conducted so the data can be used as a tool to plan prevention and help visually impaired students in the future. Objectives: To study anxiety and related factors in visually impaired students. Methods: A cross-sectional descriptive study was conducted in 77 visually impaired students by having them take 2 questionnaires in Braille; basic personal information and the Thai State-Trait Anxiety Inventory for children–Revised (STAIC-R). The data were analyzed for associations via the Chi-square test and logistic regressions to determine predictors of anxiety in the visually impaired students. Results: In all, 33.8% and 45.5% of visually impaired students are shown to have state and trait anxiety, respectively. The significant psycho-social factors related to state anxiety were educational, friend, finance, environmental, and familial factors. The basic factor related to trait anxiety was being a female. The psycho-social factors related to trait anxiety were educational and familial factors. Conclusion: They found that the significantly related psycho-social factors are education, friends, finance, environmental, and familial factors; for this reason, more concerning about psycho-social related factor in this group of people should help protect those who are susceptible to mental health issues, and promote better mental health in schools for the visually impaired.